Advancement of modification engineering in lean methane combustion catalysts based on defect chemistry. Issue 8 (29th March 2023) - Qiu, Ruishan; Wang, Wei; Wang, Zhe; Wang, Haiwang
Abstract : This review takes defect chemistry as the starting point and the improvement of material properties as the foothold, and puts forward insights on the application, limitation and prospect of defect engineering in the modification of methane combustion catalysts. Abstract : The direct emission of lean methane (0.1–1.0 vol%) into the atmosphere causes a serious greenhouse effect and energy waste. Catalytic methane combustion technology has great potential in reducing the emission of lean methane. However, the properties of catalysts affect the complete oxidation efficiency of lean methane at low temperatures. In this paper, the critical applications of defect engineering in the modification of methane combustion catalysts are mainly reviewed. Specifically, this study first introduces the characteristics and mechanisms of catalytic methane combustion reactions. Then, the types of defects and the influence of defects on catalytic performance are discussed. On this basis, the preparation strategies for defects in methane combustion catalysts are highlighted and complemented by research advances in machine learning prediction and exploration. Finally, the research challenges and opportunities for defect engineering in methane combustion catalysts are summarized. It is hoped that this review will be instructive for researchers in the reasonable and controllable construction of methane combustion catalysts with suitable defect structures for the promotion of catalytic performance.